Fracture monitoring of lightweight composite-concrete beams. (1st May 2017) - De Sutter, S.; Verbruggen, S.; Tysmans, T.; Aggelis, D.G.
Abstract: Lightweight composite-concrete beams are advantageous in terms of installation, but their mechanical and fracture behaviour is not easy to predict due to their inherent heterogeneity. In the present study hybrid beams made of Textile Reinforced Cement (TRC) hollow boxes reinforced with a Carbon Fibre Reinforced Polymer (CFRP) strip and a concrete layer on top are subjected to bending. Their fracture behaviour is complicated as they can suffer from multiple failure mechanisms: matrix cracking, interface debonding or delamination. Herein, their mechanical performance is evaluated and monitored by Acoustic Emission (AE) and Digital Image Correlation (DIC). AE indices show that beams suffering from one single failure mechanism (cement cracking) exhibit nearly constant AE characteristics throughout loading. Beams additionally suffering from delamination exhibit longer AE waveforms of lower frequency compared to the pure matrix cracking. These tendencies are obvious from the initial part of the test, enabling predictions about the subsequent failure. More importantly and for the first time in related literature, the use of DIC enables to relate AE to the strain fields during loading, the final damage pattern and the ultimate failure mechanism.